Comparative studies on the electrocatalytic hydrogen evolution property of Cu2SnS3 and Cu4SnS4 ternary alloys prepared by solvothermal method. (22nd February 2018) - Maheskumar, V.; Gnanaprakasam, P.; Selvaraju, T.; Vidhya, B.
Abstract: The development of non-precious metal based electrocatalysts is essential for Hydrogen Evolution Reaction (HER) from the splitting of water. Recently copper tin sulphide (CTS) has gained attention due to its favourable properties in photovoltaic devices and photocatalysis. In this work, CTS has been explored as an electrocatalyst in HER. Cu2 SnS3 (CTS (A)) and Cu4 SnS4 (CTS (B)) are prepared by a simple solvothermal method. From the XRD analysis, tetragonal and orthorhombic phase is confirmed for CTS (A) and CTS (B), respectively. Morphology and composition of the prepared samples has been confirmed by SEM and EDAX analysis. Optical study reveals that the band gap energy is around 1.55 and 1.20 eV for CTS (A) and CTS (B), respectively. From photoluminescence studies, CTS (B) has been observed to have a greater recombination of charge carriers than CTS (A). The prepared materials were tested and compared for its performance as electrocatalysts for HER, where the current density of CTS (A) is higher than that of CTS (B). Furthermore, the calculated Tafel slope was 98 mV/dec and 110 mV/dec for CTS (A) and CTS (B), respectively. On the other hand, CTS (A) and CTS (B) have showed good stability even after 500 cycles in acidic medium. Graphical abstract: Highlights: Cu2 SnS3 (CTS (A)) and Cu4 SnS4 (CTS (B)) electrocatalyst was successfully synthesized via a simple solvothermal method. The CTS (A) exhibit excellent activity towards hydrogen evolution reaction. The CTS (A) shows superior stability during operation in acid conditions. Compared to CTS (B), CTS (A) shows the small onset potential, a large cathodic current density and a small Tafel slope.